Pengaruh Jember Fashion Carnival Terhadap Citra Kota Jember Sebagai Destinasi Wisata Budaya - dildari, faza; Halid, Ahmad (LP2M Universitas Islam Ahmad Dahlan, 2026)
This article aims to analyze the impact of the Jember Fashion Carnival (JFC) on the image of Jember City as a cultural tourism destination. JFC is one of the largest fashion festivals in Indonesia that has gained international recognition. By presenting unique themes every year, JFC not only showcases creativity in fashion design but also serves as an event rich in artistic and cultural elements. The research method used is descriptive qualitative, with data collected through in-depth interviews, participatory observation, and document studies. The respondents of the study include tourism industry players, local government officials, artists, and tourists who have attended JFC. The research findings show that JFC has a significant and positive influence in shaping and enhancing the image of Jember City. JFC has successfully transformed the public perception of Jember from a small town into a dynamic and innovative destination. In addition, JFC serves as a main attraction that promotes Jember’s local cultural richness such as batik motifs and traditional dances through modern and spectacular interpretations. However, several challenges remain, including issues of event sustainability, waste management, and the optimization of local community participation beyond the tourism industry. In conclusion, JFC plays a strategic role as an effective cultural asset in building the image of Jember City. The recommendation is to strengthen the synergy among the government, communities, and the private sector to further develop JFC into an event that is not only aesthetically appealing but also delivers sustainable economic and social impacts for all levels of society.